Answer:
Explanation:
According to the product property of exponents :
![a^m* a^n=a^(mn)](https://img.qammunity.org/2021/formulas/mathematics/college/kuy3ln2sec6a96sd9p2qnfrvrh7qlnuzez.png)
For example :
![(5^9)(5^2)=5^(9+2)=5^(11)](https://img.qammunity.org/2021/formulas/mathematics/college/nggy5o8a1c5djg0w6qbzruiicvokqjcab9.png)
Let's take one more example :
[∵ (-)(+)=(-)]
The given expression :
![(e^2)(e^5)](https://img.qammunity.org/2021/formulas/mathematics/college/mieauyvpwgvvif4xfe5u44twvuhudgrv5g.png)
Using the product property of exponent , we get
![(e^2)(e^5)=e^(2+5)=e^(7)](https://img.qammunity.org/2021/formulas/mathematics/college/fey1v6p3hbxnim7126kg7btsk98rrtz1cq.png)
Hence, the required simplified expression would be
.